Removal of Nutrients from Fertilizer Plant Wastewater Using Scenedesmus sp.: Formation of Bioflocculation and Enhancement of Removal Efficiency - Thanh-Luu Pham; Manh Ha Bui (Journal of Chemistry)
Eutrophication of surface water has become an environmental concern in recent decades. High concentrations of nutrients, especially nitrogen- and phosphorus-rich species, have contributed to the process of eutrophication, highlighting a demand for effective and economical methods of removing nitrogen and phosphorus from wastewater. This study aimed to investigate the ability of a green microalga species, Scenedesmus sp., to remove nitrogen and phosphorus, as well as chemical oxygen demand (COD) and biochemical oxygen demand (BOD5), from fertilizer plant wastewater. Different microalgae concentrations from 10 mg/L to 60 mg/L were used to assess the growth rate, biomass production, and removal ability. The results indicated that Scenedesmus sp. grew well in the wastewater (with a growth rate from 0.3 to 0.38/day) and produced up to 70.2 mg/L of dry biomass. The algal species was able to remove ammonium (NH4+), nitrate (NO3−), phosphate (PO43−), total phosphorus (TP), COD, and BOD5 with removal rates up to 93%, 84%, 97%, 96%, 93%, and 84%, respectively. Autobioflocculation (AFL) was observed in all cultures with flocculation activity of up to 88.3% in the highest algal biomass treatment. The formation of bioflocculation enhanced the removal of nutrients, COD, and BOD5 from wastewater effluent. The results indicated that wastewater from a fertilizer plant could be used as a cost-effective growth medium for algal biomass. The autoflocculation of microalgae could be used as a more practical approach for wastewater treatment using microalgae to eliminate eutrophication.